Constitutional Dynamics in the European Union: Success, Failure, and Stability of Institutional Treaty Revisions - Dörfler, Thomas; Holzinger, Katharina; Biesenbender, Jan (International journal of public administration, 2017)
Despite high institutional hurdles for constitutional change, one observes surprisingly many EU treaty revisions. This article takes up the questions of what determines whether a treaty provision is successfully changed and why provisions are renegotiated at subsequent Intergovernmental Conferences. The article presents an institutionalist theory explaining success and renegotiation and tests the theory using all core institutional provisions by means of Qualitative Comparative Analysis. The causal analysis shows that low conflict potential of an issue is sufficient for successfully changing the treaties. Furthermore, high conflict potential of an issue and its fundamental change are sufficient for it to be renegotiated.